Antibodies against cyclic citrullinated peptides of IgG, IgA and IgM isotype and rheumatoid factor of IgM and IgA isotype are increased in unaffected members of multicase rheumatoid arthritis families from northern Sweden. Issue 6 (29th November 2011) - Ärlestig, Lisbeth; Mullazehi, Mohammed; Kokkonen, Heidi; Rocklöv, Joacim; Rönnelid, Johan; Dahlqvist, Solbritt Rantapää
Abstract : Background: Rheumatoid factors (RFs) and antibodies against cyclic citrullinated peptides (CCPs) of IgG, IgA and IgM isotype have been shown to precede disease onset by years. Objective: To evaluate serological risk markers in first-degree relatives from multicase families in relation to genetic and environmental risk factors. Methods: 51 multicase families consisting of 163 individuals with rheumatoid arthritis (RA) (mean±SD age, 60±14 years; disease duration 21 years; 71.8% female) and with 157 first-degree relatives unaffected by RA (54±17 years; 59.9% female) were recruited. Isotypes of antibodies against CCPs (IgG, IgA and IgM) and RFs (IgM and IgA) were determined using automated enzyme immunoassays. Cut-off levels were established using receiver operating characteristic curves based on values for 100 unrelated healthy controls. Results: The concentrations and frequencies of all anti-CCP and RF isotypes were significantly increased in first-degree relatives and patients with RA compared with unrelated healthy controls. The relative distribution of IgA and IgM isotypes was higher than IgG in the relatives, whereas the IgG isotype dominated in patients with RA. The patients carried human leucocyte antigen-shared epitope (HLA-SE) significantly more often than the relatives (71.4% vs 53.9%, p=0.01), while the frequency of the PTPN22 T variant was similar. HLA-SE, combined with smoking, was significantly related to all combinations of anti-CCP and RF isotypes in patients with RA. No such relationships were found for the first-degree relatives. Conclusions: All anti-CCP and RF isotypes analysed occurred more commonly in unaffected first-degree relatives from multicase families than in controls, but with different isotype distribution from patients with RA.